Corynebacterium diphtheriae - Fouch, Sarah (Henry Stewart Talks, 2025)
Characteristics of Corynebacterium diphtheriae, Biotypes of Corynebacterium diphtheriae, Clinical complications, Virulence factors and toxins, Vaccination and Control